DEVELOPMENT OF WEBTOON-BASED PHYSICS E-MODULES IN WORK AND ENERGY TOPICS ON STUDENTS' CRITICAL THINKING SKILLS - Kristina Iwung; Andi Nugraha (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to make a product in the form of a webtoon-based e-module on business and energy materials that have been tested for feasibility, effectiveness and implementation in order to be able to improve students' critical thinking skills. This form of assessment is R & D (research and development), using the ADDIE development model, namely: 1) initial needs analysis to determine student needs; 2) initial media design and making research instruments; 3) e-module development using Gacha Life and Pinterest applications, as well as validation of material experts and media experts; 4) a small-scale limited test on 22 students of class X; 5) evaluation by users are students, subject teachers and the critical thinking index used. The critical thinking index used is: analysis, interpretation, inference and evaluation. The instruments used in this study were media validation questionnaires, material validation questionnaires, and student response questionnaires. The results of the description of input from media experts and webtoon-based e-module material experts deserve to be used as a new alternative for physics learning tools. Based on the feasibility assessment from media experts, a score of 3.28 was obtained in the